Light Out‐Coupling Management in Perovskite LEDs—What Can We Learn from the Past?. (2nd July 2020) - Zhang, Qianpeng; Zhang, Daquan; Fu, Yu; Poddar, Swapnadeep; Shu, Lei; Mo, Xiaoliang; Fan, Zhiyong
Abstract: The research on perovskite light‐emitting diodes (PeLEDs) has experienced an exponential growth in the past six years. The highest external quantum efficiencies (EQEs) have surpassed 20%, 20%, and 10% for red, green, and blue colored LEDs, respectively. Considering the internal quantum efficiency is already approaching unity owing to the high material quality, the limiting factor for further improving the EQE is mainly the poor light out‐coupling efficiencies. Here, by reviewing the progress on the light out‐coupling studies for PeLEDs, organic LEDs (OLEDs), conventional semiconductor LEDs, and other special LEDs, the rational design guidelines are summarized for enhancing PeLED out‐coupling. Briefly, these design guidelines include: 1) introducing nanostructures into the active layer or tuning the thickness of it to couple out the waveguide modes, 2) adding nanostructures between the active layer and transparent electrodes to couple the waveguide modes to substrate modes, 3) adding nanostructures such as nanowires to the glass substrate to couple the substrate mode to air. Essentially, these guidelines indicate that implementing nanophotonic engineering on PeLEDs is a highly promising direction to explore, so as to substantially enhance the device performance. Abstract : Light out‐coupling efficiency is a limiting factor for further enhancing the performance of perovskite light‐emitting diodes (PeLEDs), given that the external quantum efficiencies for red, green, and blue PeLEDs have already exceeded 20%, 20%, and 10%. By reviewing the successful strategies utilized for light out‐coupling improvement for PeLEDs, organic light‐emitting diodes, etc., a set of rational design guidelines is summarized.